Proyecto de factibilidad para la implementación de una lavadora automática de vehículos livianos, con un sistema de reutilización de agua, en la ciudad de Cuenca, provincia del Azuay - Sarmiento Carpio, Fernando Patricio (2016)
This research work consists of the development of a "FEASIBILITY PROJECT FOR THE IMPLEMENTATION OF AN AUTOMATIC WASHER LIGHT VEHICLES WITH A WATER REUSE SYSTEM IN THE CITY OF CUENCA, Azuay province." For the realization of this work the following objectives: Conduct a market study to identify the supply and demand and the same needs, desires, preferences and frequency of use of the service; Carry out a technical study on the size of the company, its location, process engineering and management study; Develop an economic study to establish, costs, investments and sources of financing their credit conditions for project implementation; Perform financial evaluation of the company, using all indicators such as NPV, IRR, benefit cost ratio and sensitivity analysis to determine the profitability of the business idea. Once raised the objectives, we proceeded to follow the methodology, it referred to different methods and techniques used, such as deductive and inductive method, which allowed me to identify the specific needs of users with regard to the business idea; the historical method which could investigate the background and history on washing cars, its beginnings and in turn learn how it has evolved according to new technologies; analytical, same method that allowed a correct analysis of the information obtained in surveys. It followed the methods proceeded to determine the size of the sample, taking a part of the population under d study, being the population for this project the number of people who have light vehicles registered in the National Agency Transit Azuay, according the census of 2012, whose amount is 69,576 light vehicles. To determine the sample size, the number of people screened with light vehicles until 2025, after obtaining the current population, the corresponding formula is applied to determine the amount of surveys applied to owners of light vehicles, getting a score of 382 surveys. Once applied the methodology, it was to determine the following results: On the demand side, the number of potential plaintiffs is a total of 90%, and for year one an amount of 83,325 users, culminating in the year was determined ten with a total of 216,124 users. The amount of potential claimants per year increased by 10%. Potential applicants the sum of real plaintiffs was determined relative value being 62%, so for one year a total of 56,828 users, and culminates in the ten year a total of 133,997 users. To conclude demand the amount of effective applicants, which is 90%, ie for year one of 56,828 people who are real plaintiffs is determined, it stays with a total of 51,662 troops plaintiffs, ending in year ten, of a total of 133,997 to 120,597 real users as effective plaintiffs plaintiffs. Once the number of actual users, we proceeded with the projection of demand, taking into account the use per-capital, with an average of 40 times per year. Whereupon it came to obtain the following amounts: demand projected for year one 2`045.797; projected demand for year ten 4`823.881 users. Once completed the study of the plaintiffs, we proceeded to run the study bidders, where the amount of supply of the service was determined, which is 1`366.040 same annual services. With the data of the projected demand and supply of the service, he calculated the balance between supply and demand, which is obtained from the difference between the projected demand and supply of the service being for year one a total of 543,159 as demand unsatisfied and year ten unmet demand will 1`280.741 services. In the technical study, installed and used capacity was determined, with the installed capacity of 525,600 annual services, and the used of 31,320 annual services, with capacity utilization made the calculation of market share, ranking in year one 6% for ten year and 2% market share. He completed the technical study, proceeded to run the financial study, where to acquire detailed items: fixed assets, deferred assets and cover operating costs. Within the operating cost involved production costs and administrative expenses and sales. These items were determined on a monthly basis for investment and annually to the budget Proformado, it followed continued to establish the unit price of the service itself that for year one is $ 3.53 followed by the year five with a monetary value of $ 3.65 being for ten year cost $ 3.58 service. The cost of production according to the increased competition will place a monetary value, for the retail price same as for year one it is $ 7.00 and for the tenth year is $ 10.00. Followed the cost of service, continued with the determination of cash flows, which helped me to develop the financial evaluation, where the following results were obtained: Net Present Value $ 220,598.74; internal rate of return 30.23%; Benefit Cost Ratio 1.25 cents of profit for every dollar invested; Capital Recovery Period years 5 months and 26 days; Sensitivity analysis, the project is not sensitive to 42% increase in costs and decrease of 19% in revenue.